An analysis of the law on illicit enrichment and asset declaration in preventing corruption : The case of Malaysia - Noratikah, Muhammad Azman Ng (2025)
The growth of illicit enrichment (IE) crime is a significant challenge in combating corruption. IE is defined as a significant increase in the assets of a public officer that he or she cannot reasonably explain in relation to his or her lawful income. The secretive nature of IE makes it a complicated and argumentative crime. Hence, a well-designed and structured asset declaration (AD) system can serve as a tool to detect public officers’ wealth and effectively prevent IE. The problems addressed in this study are the lack of clarity in Malaysia’s IE law, where the current provision under Section 36 is ineffective in preventing IE, and it does not explicitly define IE as an offence, and there is no specific AD law requiring public officers to disclose their assets. The objectives of this research are to study the effectiveness of Section 36 of the MACC Act 2009, analyse the implementation of AD rules, examine IE legal frameworks from other countries, and propose improvements to Malaysia’s IE law. The researcher employed a doctrinal approach and qualitative research methodology. A semi-structured interview was conducted with expert respondents selected based on their experience with those issues. The scope of the study is limited to the issues of corruption, IE, and asset disclosure among public officers only. A comparison of provisions was also made between the current section 36 and section 10 of the Prevention of Bribery Ordinance Hong Kong, which has been presented and discussed in detail as a reference for Malaysia. To address the problem, the criminalisation of corruption indicators such as IE is necessary, and Malaysia needs to study and adopt the IE legal framework from Hong Kong. The findings of this study indicate that Malaysia lacks a clear and specific provision on IE, as well as a specific AD law requiring public officers to disclose their assets. In fact, the clandestine nature of illicit enrichment crimes and the ineffectiveness of section 36 have identified several issues, challenges, and weaknesses in the wording, application and implementation of section 36. The proposed recommendations to address the issues suggest implementing the revised version of section 36 and enacting a new provision to mandate AD in Malaysia to fight corruption effectively